Moisture retention characteristic of red and forestry soil of Kerala - Reena Mathew (Department of Agronomy, College of Horticulture, 1985)
The investigation was undertaken in the College of Horticulture, Vellanikkara, during the period from November 1983 to September 1984. Soil samples were collected from Cannanore, Calicut and Trivandrum districts for red soil and Trivandrum, Trichur and Wynad districts for forest soil. Moisture retention studies were done at six applied pressures viz. 0.3, 1, 3, 5, 10 and 15 bars and these values were correlated with contents of textural separates and organic carbon using multiple regression analysis. The study revealed that moisture retention by 2 mm sieved soil was higher for forest soil than red soil at all the six tensions. The moisture contents on weight basis at 0.3 bar for the two soils were 24.85 and 10.45 per cent, respectively. The corresponding values at 15 bars were 18.15 and 7.21 per cent. In both the soil, the contents of fine fraction (clay and silt) showed significant positive correlation with moisture retention while the correlation with fine sand was significant and negative. Organic carbon was found to have no bearing on moisture retention as indicated by the lack of significant correlation at any of the tensions studied. The gravel fraction in the case of forest soil was found to retain moisture and the values at field capacity and permanent wilting point were 10.8 and 9.46 per cent, respectively. The moisture retention of the soil including gravel amounted to 26.90 per cent at field capacity and 20.2 per cent at permanent wilting point, on volume basis. Prediction equations were developed to estimate the moisture retention at 0.3 and 15 bars of the 2 mm sieved soil from a knowledge of the contents of organic carbon and textural constituents. In the case of forest soil, another set of prediction models was also worked out to arrive at the moisture retention including gravel at these soil moisture constants.